Novel Single-Photon Differential Phase-Shift Keying With Asymmetric High-Bit-Rate Coding and Low-Bit-Rate Gated Receiving Coding Data Format - Hu, Kuan-Wei; Cheng, Chih-Hsien; Matsumoto, Atsushi; Akahane, Kouichi; Wu, Jau-Yang; Wu, Yuh-Renn; Lin, Gong-Ru (Journal of lightwave technology, 2024)
A novel single-photon differential phase-shift keying (DPSK) scheme with asymmetric high-bit-rate coding (at 192 Mbit/s) and low-bit-rate gating (1 Mbit/s) coding data format is proposed to stabilize the long-term and long-distant point-to-point secure communication over 40-km standard single-mode-fiber (SSMF). The single-photon carrier is served by an attenuated distributed-feedback laser diode with ultralow phase and power fluctuations of Δθ/θ<0.005% and ΔP/P<0.01%. The single-photon carrier successively encoded with pulsed return-to-zero (RZ) clock and DPSK bits at 192-Mbit/s is decoded by a synchronized one-bit-delay interferometer at 192-Mbit/s with enhanced immunity to spectral and thermal noise. The single-photon DPSK data is detected within 1-ns transistor-transistor logic (TTL) gated window at 0.1% duty-cycle of the 1-Mbit/s receiver. Such an asymmetric DPSK encoding and receiving coding data format further stabilize the single-photon DPSK codes with a quantum bit error ratio (QBER) of 0.038% when the interfered free spectral range of 4.8 MHz expands broader than the linewidth of the single-photon carrier of 293 kHz to ensure the interferometric visibility of 99.2% with the operating time beyond 1065 s. Decoding the single-photon DPSK bits with an average photon number of 0.2 #/bit guarantees the BER at 1.5% with a secure key rate of 113.4 kbit/s under the back-to-back transmission, and remains the BER at 3.2% with a secure key rate of 10.1 kbit/s over 40-km-SSMF transmission. The low-bit-rate-gated receiving of high-bit-rate transmitted DPSK coding data format has unveiled a novel stabilization scheme for single-photon secure communications.